FAKTOR YANG MEMPENGARUHI KONSUMSI SAYUR DAN BUAH REMAJA DI SMP NEGERI 238 JAKARTA - Chika Meidiana Amelia; Adhila Fayasari (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Vegetables and fruit are generally food groups that are consumed by many people because many contains of benefits. Even though, in Indonesia consumption of vegetables and fruit still less than recommendation. The purpose of this research is to identify the factors affecting the consumption of vegetables and fruit adolescent at SMP NEGERI 238 Jakarta. This research uses design cross sectional and sampling using system random sampling that gets 107 students class VII, VIII, and IX in January 2020. The data obtained is based on the result of the questionnaire, form SQ-FFQ and Recall 24hour. Statistic data analysis used chi-square and logistic regression test. The result of this study indicate that adolescent who consumed vegetables and fruit according to recommendations per day are 24,3%. Bivariate result indicate there were significant relationship between self efficacy (p = 0,034), availability vegetables and fruit (p = 0,048), parental influence (p = 0,032), and there is no significant relationship between knowledge (p= 0,063). Multivariate result indicate there were signification relationship between knowledge, self efficacy, availability vegetables and fruit, and parental influence to consumption of vegetables and fruit, with highest OR value 5,634 on parental influence.